Childhood Wasting in Bangladesh: An Analysis of Trends and Determinants from Demographic and Health Surveys (2007-2018) - Islam, Tanjirul; Anni, Tayeeba Tabussum; Hassan, Sakib Al; Jui, Mahmuda Akter; Moon, Mymuna Islam; Islam, Md Amirul (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
Aim: Childhood wasting is a significant public health issue throughout the world, notably in developing countries. 8.4% of Bangladeshi young children under five years old are currently wasted, which has an effect on the country's overall public health outcomes. The study's aim was to determine childhood wasting among under five years old in Bangladesh. Methods: The study's dataset was obtained from the country-wide Bangladesh Demographic Health and Survey (BDHS) in 2017–2018. The study sample contained 30,830 under-five children. The associations between specific independent factors and nutritional status were assessed using chi-square tests, and the risk factors associated with early childhood wasting were found using binary logistic regression. Results: The majority of the children (51.6%) in the study's sample were male, and they resided in rural areas the most often. From 17% in 2007 to 8% in 2017, the frequency of childhood wasting has reduced over time. The study also discovered that mothers' overweight/obese and underweight body mass indices, as well as their relative age (24–35 months and 36–47 months), were risk factors linked to childhood wasting in Bangladesh. Conclusion: This study presents the significant risk factors for severe child wasting in Bangladesh. Countries that suffer from childhood malnourishment may use the findings of this study for further research.